Precarious scientific publication amongst Peruvian medical specialists: Analysis of results in Google Academics and Scopus - Mejía, Christian R. (2021)
Introduction: In industrialized countries there is large production of publications from specialized physicians on specific topics regarding their working areas. Reality is quite different in Peru. Objective: To determine the rates of scientific paper production found in Google Academics and Scopus, as well as their association with medical specialties. Methodology: This is an analytical cross-section study. Randomized sampling of medical specialists registered in the Peruvian College of Physicians was performed. Those who were selected were searched aiming to determine whether they had produced papers in publications that would be found in Google Academics or that would be indexed in the Scopus database. Their lifetime production was reported, together with statistical associations. Results: Out of 2108 specialized physicians, 1810 (85.9%) and 2027 (96.2%) had never produced any scientific publication that could have been found in Google Academics or in Scopus indexed journals, respectively. Specialties most frequently found in Google Academics were as follows: gastroenterology (46.3%), dermatology (44.4%), and neurology (42.5%). In Scopus, most frequently found specialties were neurology (15.0%), gastroenterology and dermatology (11.1%, both), and pathology (10.9%). The highest number of production in foreign Scopus-indexed publications was 4 original papers for a corresponding author. There were statistically significant associations with respect to the lowest numbers of Scopus-indexed publications for 15 specialties (p<0.042 for all), and thirteen of them featured no scientific production at all. Conclusions: The low number of authors who published scientific papers was surprising, and this may serve as an alert about the low resources available for generating and publishing their research, so strategies for helping in this purpose should be established.